Orbital Apex Syndrome in a diabetic patient, Is It Tolosa Hunt? Poster Presentation - Case Report - Ophthalmologist - MADE PARAMITA WIJAYATI; AA Mas Putrawati (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : The presence of that specific sign in neuro ophthalmology cases can easily determine the differential diagnosis. But the challenge is how do we found the cause. We describe a case of visual loss with ophthalmoplegia in a diabetic patient suspected of having Tolosa Hunt syndrome. Case Illustration : Woman, 63 years old with acute visual loss and feel a "heavy eyelid" in the left eye for 2 weeks. The Visual Acuity is no light perception on the left and ophthalmoplegia with mild proptosis. We do the laboratory test and MRI. No specific result of infection was found but the patient was diagnosed with diabetes mellitus (DM) type 2. MRI shows a lesion in the left cavernous sinus. Diagnosis of Orbital Apex syndrome was made. We give the patient a high dose of steroid and then continue with prednisone orally. In 24 hours after treatment the "heavy eyelid" decreased. One month after therapy there are improvements in eye movement but still no light perception. Discussion : In cases of orbital apex syndrome with DM, we need to consider mucormycosis as the cause. In this case, the symptoms and signs as well as the MRI led to a Tolosa Hunt. Steroid administration was able to reduce heavy eyelids and cranial nerve palsy even though visual acuity had not improved after 1 month of therapy. Conclusion : Laboratory test and Neuroimaging plays an important role to find out the cause. High-dose steroid therapy in a diabetic patient with Tolosa Hunt Syndrome can be given with tight hyperglycemic control.